IMPLEMENTASI ALGORITMA WELCH-POWELL TERHADAP PENGATURAN LALU LINTAS PERSIMPANGAN JALAN DALAM MENGATASI KEMACETAN - Rina Filia Sari; Hendra Cipta; Esto Fanny Munthe (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2022)
The traffic is one of the problems that are often in big cities in Indonesia, where this also happened on Gatot Subroto Sei Sikambing street, Medan city. The traffic light is a tool that is made with the aim of being an assistant in regulating traffic so that it runs more orderly, but it has not been able to run optimally due to the determination of which traffic flow is green or red and also the duration of the traffic light. The solusition that can be given to solve this problem is to use a welch-powell algorithm. The welch-powell algorithm is doing coloring activity  by producing a chromatic number. This is study, the chromatic number obtained was 4 and the average duration of the red light has decreased by  or 116.51 seconds so that its negative and the average duration of the green light has increased by or 119.63 seconds so its positive